GAMBARAN TINGKAT KECEMASAN KORBAN GEMPA LOMBOK - PURQOTI, DEWI NURSUKMA; thoyyibah, zurriyatun; OKTAVIANA, ELISA (Jurnal Persatuan Perawat Nasional Indonesia (JPPNI), 2019)
Earthquakes are consistently proven to relate of mental health issues such as anxiety, depression and post-traumatic stress disorders immediately after disaster. This condition will deteriorate if not detected early and well handled, so it requires mental health services (trauma healing). Excessive anxiety can have a detrimental impact on the mind as well as the body can even cause physical illness. Objectives: The study aims to determine the level of anxiety victims of Lombok earthquake. Methods: This research is a descriptive study with a cross sectional approach. Sampling techniques used by Purposive Sampling with a sample number of 40 people. Data analysis used is univariate with data presented in narrative form, frequency distribution table and percentage. Results: The results showed that 15 respondents experienced mild anxiety (37.5%) and 25 respondents experienced moderate anxiety (62.5%).  Discussion: In addition to physical impact, earthquake incidence also raises mental health problems, one of which is anxiety. Anxiety is a response to a specific situation that threatens and is a normal thing to happen. The instruments used in this study are the Hamilton Anxiety Rating Scale (HARS) questionnaire. Anxiety in the medium category still experienced by respondents can be influenced by gender, age, level of education and experience in the event of an earthquake. Conclusion: most of the respondents in this study is still experiencing moderate anxiety.